Integration of Local Wisdom-Based Gymnastics in English Literature Learning as an Effort to Enhance Students’ Literacy and Health - Uci Dwi Cahya; Ema Julianda; Dede Gustian (Jurnal Pendidikan dan Sastra Inggris, 2026)
This study aims to examine the integration of local wisdom-based gymnastics in English Literature learning for Junior High School (SMP) students as an effort to increase student learning engagement and cultural literacy. English Literature learning is often considered less interesting due to the dominance of conventional methods that focus on text, so that learning innovations are needed that are more interactive, contextual, and in accordance with student characteristics. This study uses a descriptive qualitative approach with research subjects of grade VIII SMP students. Data collection techniques were carried out through observation, interviews, and documentation to obtain a comprehensive picture of the learning process and student responses. The results of the study indicate that the integration of traditional gymnastics containing elements of movement, music, and local cultural values ​​​​can increase student active participation during the learning process. Students appeared more enthusiastic, motivated, and bold in expressing opinions when discussing English literature. In addition, this activity helps students understand the cultural values ​​​​contained in local wisdom and in foreign literary texts through a simple process of cultural comparison. The embodied learning approach applied also makes it easier for students to interpret the meaning of texts in a more concrete and contextual way through direct movement experiences. In addition to improving academic aspects, the integration of local wisdom-based gymnastics has a positive impact on physical health, learning concentration, and a more enjoyable and conducive classroom atmosphere. Students become more focused and have positive energy in participating in learning. Therefore, the integration of local wisdom-based gymnastics can be an innovative, creative, and relevant learning strategy for implementation in English Literature instruction in junior high schools to support the strengthening of character, culture, and student learning outcomes.